La politique commerciale de George W. Bush : rupture ou continuité ? - Jean-Baptiste Velut (Revue LISA)
This article offers a critical assessment of American trade policy under George W. Bush. It begins by comparing his views and political ambitions with those of his Democratic predecessor, Bill Clinton, before highlighting the new political and economic context of the 2000s. These elements provide crucial background, first to study the evolution of America’s relations with its top trading partners and second to analyze the strategy of “competitive liberalization” undertaken by the administration at the multilateral, regional and bilateral levels. This article has two objectives: 1) determining trends of continuity and change between George W. Bush and his predecessor; 2) assessing the trade policy initiatives undertaken by the Republican administration in order to understand the domestic and international challenges with which the next President of the United States will be confronted.